2015
DOI: 10.1007/s11661-015-3285-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prior Athermal Martensite on the Isothermal Transformation Kinetics Below M s in a Low-C High-Si Steel

Abstract: A. NAVARRO-LÓ PEZ, J. SIETSMA, and M.J. SANTOFIMIA Thermomechanical processing of Advanced Multiphase High Strength Steels often includes isothermal treatments around the martensite start temperature (M s ). It has been reported that the presence of martensite formed prior to these isothermal treatments accelerates the kinetics of the subsequent transformation. This kinetic effect is commonly attributed to the creation of potential nucleation sites at martensite-austenite interfaces. The aim of this study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 27 publications
5
51
0
3
Order By: Relevance
“…It was found that the transferring of carbon atoms from supersaturated PM to RA is inhomogeneous along the γ / α ’ interface (see Figure c) . The region adjacent to carbides tends to exhibit a low carbon content because carbon atoms (C‐depleted region) have been consumed inside PM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the transferring of carbon atoms from supersaturated PM to RA is inhomogeneous along the γ / α ’ interface (see Figure c) . The region adjacent to carbides tends to exhibit a low carbon content because carbon atoms (C‐depleted region) have been consumed inside PM.…”
Section: Resultsmentioning
confidence: 99%
“…A new process of forming a prior phase, such as martensite (PM) before the bainitic transformation has seen increasing attraction. Navarro‐López et al have pointed out that PM can aid bainite transformation kinetics by creating potential nucleation sites at martensite‐austenite interfaces in addition to austenite boundaries . The PM promotes BF nucleation rate by at least two orders of magnitude at the beginning of isothermal holding compared with full‐bainite microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Si and Al elements in the spring steel can inhibit the precipitation of cementite in the Q&P process,E.P.Da Siva, D.De knijf, D.V.Edmods and Moor [5][6] all indicate that carbides precipitation in the partition period cannot be completely suppressed even in low carbon steels with relatively high Si and Al content, especially transition carbides [7][8].While precipitation of carbides and the diffusion of carbon in martensite into austenite are a competition mechanism.Carbides precipitation not only lead to the less content of retained austenite at room temperature, but also contribute to poor carbon in martensite,which can reduce comprehensive mechanical properties.As the second phase particle precipitation, the size of carbides will affect the mechanical properties of steel [9][10].The large size carbide particles formed in partition time are easy to cause stress concentration, reduce the plasticity and toughness,and it will result in serious brittle fracture.So,in addition to martensite,precipitation of carbides is also an important factor determining the mechanical properties of spring steel treated by Q&P process [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It mainly work in bending periodic, alternating torsion stress conditions, subjected to pull, pressure, shock, torsional fatigue, corrosion and other effects, sometimes bear high short-term sudden load. So the comprehensive mechanical properties of spring steel high requirements.The microstructure of martensite and retained austenite can be obtained by heat treatment of spring steel by Q&P process, and it has the advantages of both high strength and high plasticity in performance [1][2][3][4].Although the Si and Al elements in the spring steel can inhibit the precipitation of cementite in the Q&P process,E.P.Da Siva, D.De knijf, D.V.Edmods and Moor [5][6] all indicate that carbides precipitation in the partition period cannot be completely suppressed even in low carbon steels with relatively high Si and Al content, especially transition carbides [7][8].While precipitation of carbides and the diffusion of carbon in martensite into austenite are a competition mechanism.Carbides precipitation not only lead to the less content of retained austenite at room temperature, but also contribute to poor carbon in martensite,which can reduce comprehensive mechanical properties.As the second phase particle precipitation, the size of carbides will affect the mechanical properties of steel [9][10].The large size carbide particles formed in partition time are easy to cause stress concentration, reduce the plasticity and toughness,and it will result in serious brittle fracture.So,in addition to martensite,precipitation of carbides is also an important factor determining the mechanical properties of spring steel treated by Q&P process [11][12].There were no systemic study of precipitation of spring steel in the partition of carbides and its effects on the mechanical properties in the domestic and foreign literatures.The purpose of the present work was to explore the influence ofcarbides on mechanical properties by the statistics of carbides precipitation types, quantity and size distribution of spring steel after different Q&P processes,and calculate the contribution to strength.It is determined that In addition to the changes in mechanical properties caused by different tissue structures, the contribution of carbides precipitation strengthening is confirmed ,which can provide guidance for optimizing mechanical properties. …”
mentioning
confidence: 99%
“…В настоящее время получением бейнитной структуры, в частно-сти нижнего бейнита, занимается большое количество исследователей [1][2][3][4]. Такой интерес вызван высоким комплексом характеристик ме-ханических свойств, которые сталь приобретает в результате формиро-вания такой структуры.…”
Section: Introductionunclassified